2003
DOI: 10.1037/1076-898x.9.2.101
|View full text |Cite
|
Sign up to set email alerts
|

The influence of schemas, stimulus ambiguity, and interview schedule on eyewitness memory over time.

Abstract: The authors examined how a crime schema influenced the types of details witnesses recalled over multiple interviews that varied in delay before the initial interview and between subsequent interviews. Accuracy data showed that, in general, schema-irrelevant traces experienced greater decay than schema-consistent and schema-inconsistent traces after the initial interview and that delaying the initial interview negatively affected recall at the initial interview but led to less decay over subsequent interviews. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
99
2
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 45 publications
5
99
2
1
Order By: Relevance
“…They have typically found that schema-inconsistent items are remembered better than schema-consistent items, at least in recognition memory (Graesser et al, 1979;Lampinen et al, 2001;Neuschatz et al, 2002;Shapiro & Fox, 2002). Similarly, researchers have also found that, when asked to make remember-know judgements, participants assign more remember judgements to schema-inconsistent items than to schema-consistent items (Lampinen al., 2000;Lampinen et al, 2001;Tuckey & Brewer, 2003). Therefore, our finding that the latter effect extends to schema-inconsistent versus schema-consistent life script events establishes that the effect of schemata on the phenomenological properties of recollection holds for the life script as well.…”
Section: Complementary Findingssupporting
confidence: 63%
See 3 more Smart Citations
“…They have typically found that schema-inconsistent items are remembered better than schema-consistent items, at least in recognition memory (Graesser et al, 1979;Lampinen et al, 2001;Neuschatz et al, 2002;Shapiro & Fox, 2002). Similarly, researchers have also found that, when asked to make remember-know judgements, participants assign more remember judgements to schema-inconsistent items than to schema-consistent items (Lampinen al., 2000;Lampinen et al, 2001;Tuckey & Brewer, 2003). Therefore, our finding that the latter effect extends to schema-inconsistent versus schema-consistent life script events establishes that the effect of schemata on the phenomenological properties of recollection holds for the life script as well.…”
Section: Complementary Findingssupporting
confidence: 63%
“…Thus, in addition to further studies on room schemata (Lampinen, Copeland, & Neushatz, 2001;Nemeth & Belli, 2006;Pezdek et al, 1989), researchers have probed for the mnemonic influence of schemata for eyewitness-related material, such as crime scenes (Holst & Pezdek, 1992;List, 1986;Smith & Studebaker, 1996;Tuckey & Brewer, 2003);…”
Section: Shapes Memory For Fictional Life Storiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Hekkanen & McEvoy, 2005;Luna & Migueles, 2008;Roediger, Meade & Bergman, 2001) and false memory effects (e.g. GarciaBajos & Migueles, 2003;Holst & Pezdek, 1992;Tuckey & Brewer, 2003a, 2003b have been demonstrated in eyewitness paradigms with typical individuals. However no research to date has examined this with witnesses with high-functioning autism, despite their well-documented difficulties in event memory and memory organisation.…”
mentioning
confidence: 99%